Experimental research on production law of multilayer heterogeneous reservoirs - Deng, Xuan; Huang, Xiaoliang; Ye, Qing; Li, Sainan; Yu, Chengchao; Zhang, Xu; Wang, Zuohao (Frontiers in Earth Science, 2022)
In the development of multi-layer co-production heterogeneous reservoirs, problems such as strong inter-layer heterogeneity and serious interference always exist, resulting in an unclear understanding of inter-layer production rules. A clear understanding of the interference mechanism and influence law of the main controlling factors of multi-layer heterogeneous reservoirs on the production of small layers is the key to the effective development of such reservoirs. On the basis of clarifying the main controlling factors affecting the production of multi-layer heterogeneous reservoirs, this paper develops a multi-pipe parallel displacement experiment system to carry out indoor heterogeneous reservoir multi-layer water injection flooding experiments. Combined with dynamic and static parameters, the experiments simulate and evaluate the effects of factors such as different permeability ratios, different water cuts, shutting down high permeability layers, production pressure differences, and changes in crude oil viscosity of high permeability layers on interlayer production. The primary objective of this work is to reveal the mechanism of small-layer interference under different conditions, and clarify the law of influence of main control factors on the production of small-layer. The research results show that the smaller the permeability ratio, the weaker the difference in physical properties among layers along the vertical direction. The reduction in the difference in seepage resistance will decrease the dynamic interference among layers. The reduction in the water ratio among layers and shutting down high permeability layers can reduce the interlayer interference effectively. Increasing production pressure difference will effectively improve the oil displacement efficiency of reservoirs with poor physical properties. A lower fluidity in the high permeability layers can effectively improve the oil displacement efficiency of other layers.